A Comparison between Effects of Theater-Based Art Therapy and Solution-Focused Therapy on Social Adjustment in Students with Low Academic Achievement - Tabatabaee Salehi, Behnoush; Dortaj, Fariborz; Sadeghi, Jamal; Akbarnattaj Shob, Nabiollah; Mohammadzadeh Edmellaee, Rajabali (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to compare the effects of theater-based art therapy (TRT) and solution-focused therapy (SFT) on social adjustment in students with low academic achievement.Methods and Materials: A quasi-experimental methodology with a pretest/posttest design and an unmatched control group was adopted. The statistical population consisted of female students of lower-secondary high schools in grade 9 with low academic achievement (GPA